Women’s traumatic experience in a permanent shelter after volcanic mud flow in Magelang, Indonesia - Purborini, Nurul; Amin, M. Khoirul (International Journal of Research in Medical Sciences, 2017)
Background: A natural disaster event may cause property loss and affect people’s health. Shelters are arranged for victims to live after disasters. Living in shelters is recognized as traumatic experiences, especially women. Psychological changes may occur due to disaster impact. Methods: This study was qualitative study using phenomenology approach. In this qualitative study, participants were recruited at a permanent shelter in Magelang. The qualifying participants were met the inclusion and exclusion criteria. Data collection using recorder, interview guideline, and field note. Results: 5 women (age 21-50) were involved in this study. In theme analyses, the results found four themes related to women’s traumatic experiences after volcanic mud flow. The themes were psychology respond, cognitive respond, social interaction, and meaning of live. Conclusions: Women who lived in permanent shelters have greater risk for traumatic experiences. Reducing the risk is needed. Government and social organization need to work together to provide some activities that suitable for women. By doing some activities, women can improve their social interaction with neighbourhood. Increasing the social interaction can help women to cope with stressful condition. Improving social interaction also can reduce the traumatic feeling because women can share their experiences with others.